(untitled) (Journal of Health, Population and Nutrition, 2010)
The study assessed the timing and causes of neonatal deaths in a rural area of Bangladesh. A populationbased demographic surveillance system, run by the International Centre for Diarrhoeal Disease Research, Bangladesh, recorded livebirths and neonatal deaths during 2003-2004 among a population of 224,000 living in Matlab, a rural subdistrict of eastern Bangladesh. Deaths were investigated using the INDEPTH/ World Health Organization verbal autopsy. Three physicians independently reviewed data from verbal autopsy interview to assign the cause of death. There were 11,291 livebirths and 365 neonatal deaths during the two-year period. The neonatal mortality rate was 32.3 per 1,000 livebirths. Thirty-seven percent of the neonatal deaths occurred within 24 hours, 76% within 0-3 days, 84% within 0-7 days, and the remaining 16% within 8-28 days. Birth asphyxia (45%), prematurity/low birthweight (15%), sepsis/meningitis (12%), respiratory distress syndrome (7%), and pneumonia (6%) were the major direct causes of death. Birth asphyxia (52.8%) was the single largest category of cause of death in the early neonatal period while meningitis/ sepsis (48.3%) was the single largest category in the late neonatal period. The high proportion of deaths during the early neonatal period and the far-higher proportion of neonatal deaths caused by birth asphyxia compared to the global average (45% vs 23-29%) indicate the lack of skilled birth attendance and newborn care for the large majority of births that occur in the home in rural Bangladesh. Resuscitation of newborns and management of low-birthweight/premature babies need to be at the core of neonatal interventional packages in rural Bangladesh. Key words: Causes of death; Interventions; Neonatal mortality; Verbal autopsy; Bangladesh DOI: 10.3329/jhpn.v28i4.6044 J HEALTH POPUL NUTR 2010 Aug;28(4):375-382